Coloured cornea replacements with anti-infective properties: expanding the safe use of silver nanoparticles in regenerative medicine. Issue 12 (7th March 2016) - Alarcon, E. I.; Vulesevic, B.; Argawal, A.; Ross, A.; Bejjani, P.; Podrebarac, J.; Ravichandran, R.; Phopase, J.; Suuronen, E. J.; Griffith, M.
Abstract : A methodology that allows safe incorporation of nanosilver in collagen hydrogels is reported in this work. Abstract : Despite the broad anti-microbial and anti-inflammatory properties of silver nanoparticles (AgNPs), their use in bioengineered corneal replacements or bandage contact lenses has been hindered due to their intense yellow coloration. In this communication, we report the development of a new strategy to pre-stabilize and incorporate AgNPs with different colours into collagen matrices for fabrication of corneal implants and lenses, and assessed their in vitro and in vivo activity.